Técnicas de identificação de defeitos da cromatina espermática de touros (Bos taurus) e sua correlação com a eficiência da produção in vitro de embriões (PIVE) - Silva, Matheus Vicente da (2022)
Currently, bovine semen tests provide a limited degree of prognostic and diagnostic information on fertility, which demonstrates the need for sperm function tests, including analyses of chromatin integrity. In this context, it is proposed to evaluate the performance of different techniques for identifying sperm chromatin defects in bulls (Bos taurus) and to correlate the results with the cleavage rate and blastocyst formation in routines of in vitro embryo production (IVP), with the aim of identifying the most efficient, lowest-cost and easy-to-apply methods in the field and in animal reproduction laboratories. Four samples of semen frozen in TRIS-yolk medium from four Girolando bulls (Bos taurus) with different degrees of fertility were used. These samples were submitted to sperm chromatin evaluation by different techniques: visual and computational evaluation of smears stained with toluidine blue (TB) and with Feulgen reaction (FR), visual evaluation of smears stained with acridine orange (AO) under fluorescence microscopy and confocal laser scanning microscopy, evaluation in transmission electron microscopy (TEM) and SCSA (sperm chromatin structure assay). The same samples were used in routine in vitro embryo production, from which cleavage and blastocyst rates were calculated. The results obtained in each technique were correlated with each other and with the cleavage and blastocyst rates. In general, all the chromatin alterations identified by any method presented greater correlations with the blastocyst rate than with the cleavage rate, possibly because the chromatin alterations interfere more in the early embryonic development than in the fertilizing capacity of the embryos. sperm. Among the methods tested, the evaluation of chromatin alterations by transmission electron microscopy (TEM) and staining with acridine orange (AO) evaluated by fluorescence microscopy and confocal laser scanning microscopy were the most effective to identifyin identifying chromatin alterations. that interfere with the efficiency of in vitro bovine embryo production. However, TEM is very expensive. The techniques that use smears stained with AT and Feulgen, despite being less effective than TEM and AO, are the least expensive and can be used with relative effectiveness.